CORRELATION BETWEEN BODY MASS INDEX AND INTRAOCULAR PRESSURE AT PRIMASATYA HUSADA CITRA HOSPITAL, SURABAYA - Titiek Ernawati; Rofiqi Rofiq; Okky Imanuel Samatha; Lani Diana (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Background: Obesity currently becomes a major public health problem globally with the increasing prevalence in most countries. In some studies, an increase in body mass index above normal values has been suggested as an independent risk factor associated with increased intraocular pressure, which can progress to glaucoma. Objective: To analyze the relationship between body mass index and intraocular pressure. Material and Method: The design of this study was cross-sectional with a observational analytic approach, which was conducted during the period September-October 2021, at Primasatya Husada Citra Hospital, Surabaya. The statistical analyses were done using SPSS 22.0. P value of 0.05 or less was considered statistically significant. Result: The study of 100 subjects found significant difference in intraocular pressure in both right and left eyes between subjects with normal, overweight, and obese. This study also found a positive correlation between BMI and intra-ocular pressure of the right eyes and left eyes. Conclusion: Our result show that there was a statistically significant relationship between increased BMI and intraocular pressure. An increase in BMI is associated with an increase in intraocular pressure.